THE INTEGRATION OF PHARMACOLOGICAL AND NON-PHARMACOLOGICAL APPROACHES IN THE TREATMENT OF HEART FAILURE - O`ktamova N.B; Boymuratov F.T (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: Heart failure is a complex clinical syndrome characterized by the heart’s inability to pump sufficient blood to meet the body’s metabolic demands. Despite major advances in pharmacotherapy, the condition remains a leading cause of morbidity and mortality worldwide. Effective management requires a comprehensive approach that combines pharmacological and non-pharmacological strategies. Pharmacological treatment focuses on improving cardiac output, reducing neurohormonal activation, and controlling symptoms through agents such as ACE inhibitors, beta-blockers, diuretics, and mineralocorticoid receptor antagonists. Non-pharmacological measures, including lifestyle modification, salt and fluid restriction, weight management, and regular physical activity, significantly improve quality of life and reduce hospitalization rates. This article reviews the synergistic role of these two therapeutic modalities in optimizing heart failure outcomes and emphasizes the importance of patient education and multidisciplinary care in ensuring long-term treatment success.